A influência da liderança das PME portuguesas na Inovação - Fontan, Orlando (2015)
Submitted by Marlene Nunes (marlene-isabel.nunes@europeia.pt) on 2015-06-30T12:00:38Z No. of bitstreams: 1 T-MEG_14_07_Orlando Fontan.pdf: 2076359 bytes, checksum: 53dadd353ba448fd7d979dedc13a42ef (MD5)